External electric field effect and impact of encapsulating matrix on optical and electronic properties within CdSe/ZnSe core/shell QDs. (25th August 2021) - Jbeli, A; Yahyaoui, N; Zeiri, N; Said, M
Abstract: In this study, we have carried out a theoretical investigation of CdSe/ZnSe core/shell spherical quantum dot (CSQD) embedded in different dielectric matrix. The effect of surrounding matrix and the external electric field on the linear and third-order nonlinear real and imaginary parts of the dielectric function have been simulated numerically using the effective mass approximation and taking into account the compact density matrix approach. The electronic band structure and corresponding wave functions were calculated by solving the Schrödinger equation in the framework evoked previously. The study revealed a significant blue shift of the transition energies under electric field offering the possibility of adjusting them. In addition, by varying the dielectric matrices enveloping our main structure, it was also found that the choice of the pattern of the matrix is fundamental for the manipulation of the resonance peak energies of the dielectric function.